Invasion and control of water hyacinth (Eichhornia crassipes) in China - Chu, Jian-jun (Zhejiang University Press, 2006)

(untitled)
By the time of primary 21st century, water hyacinth had become a serious environmental problem in China. Water hyacinth contributes to the major part of ecological hazards from the invasion of foreign plant species, which is estimated about USD 7 billion a year in values. In the past 10 years, herbicides glyphosate, 2,4-D and paraquat have been used in controlling water hyacinth in China. Although the herbicides provided effective control on the weed in some areas, they could not provide the sustainable inhibition on the weed population, while would lead to pollution on water at various levels. At present, the herbicide application on water hyacinth is forbidden in many areas of China such as Shanghai. In this situation, the asexual reproduction inhibitor, KWH02, was invented for controlling water hyacinth and it provided about 70% of growth inhibition without any risk of dead plant pollution. It has been about 10 years for bio-control of water hyacinth in China. Works focused on mainly the efficacy and safety of the utilization of foreign insects. Researches on microorganism herbicides to control water hyacinth were started and obtained primary achievements in recent years. Although there are different opinions on how to face the water hyacinth problem in China, it is accepted widely that the control methods should be high efficient and safe with low cost. Some practical measures for integrated management of water hyacinth are suggested.